Sequencing Reveals miRNAs Enriched in the Developing Mouse Enteric Nervous System - Christopher Pai; Rajarshi Sengupta; Robert O. Heuckeroth (Non-Coding RNA, 2023)
The enteric nervous system (ENS) is an essential network of neurons and glia in the bowel wall. Defects in ENS development can result in Hirschsprung disease (HSCR), a life-threatening condition characterized by severe constipation, abdominal distention, bilious vomiting, and failure to thrive. A growing body of literature connects HSCR to alterations in miRNA expression, but there are limited data on the normal miRNA landscape in the developing ENS. We sequenced small RNAs (smRNA-seq) and messenger RNAs (mRNA-seq) from ENS precursor cells of mid-gestation Ednrb-EGFP mice and compared them to aggregated RNA from all other cells in the developing bowel. Our smRNA-seq results identified 73 miRNAs that were significantly enriched and highly expressed in the developing ENS, with miR-9, miR-27b, miR-124, miR-137, and miR-488 as our top 5 miRNAs that are conserved in humans. However, contrary to prior reports, our follow-up analyses of miR-137 showed that loss of Mir137 in Nestin-cre, Wnt1-cre, Sox10-cre, or Baf53b-cre lineage cells had no effect on mouse survival or ENS development. Our data provide important context for future studies of miRNAs in HSCR and other ENS diseases and highlight open questions about facility-specific factors in development.